2011
DOI: 10.1097/rlu.0b013e318212c525
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid SPECT/CT for Attenuation Correction of Stress Myocardial Perfusion Imaging

Abstract: Attenuation correction using Hybrid SPECT/CT improved specificity in the right coronary artery, but decreased specificity in the left anterior descending. This technique is likely to be more useful in men than in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 19 publications
3
21
0
Order By: Relevance
“…An improved detection rate of the left anterior descending CAD was also reported by Shotwell et al [5] Improvement of specificity the detection of stenosed LAD observed in our study indicates that AC did not introduce additional artefacts in the anterior wall of myocardium, an argument that is raised by authors against application of AC [17]. Several authors have reported such artefacts [18,19], including recently Huang et al [10], who observed a reduction of specificity in anterior wall as an effect of AC. Such artefacts are thought to be the effect of overcorrection of the inferior wall [18,19], causing a relative reduction of counts in anterior wall, leading to induction of false perfusion defects.…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…An improved detection rate of the left anterior descending CAD was also reported by Shotwell et al [5] Improvement of specificity the detection of stenosed LAD observed in our study indicates that AC did not introduce additional artefacts in the anterior wall of myocardium, an argument that is raised by authors against application of AC [17]. Several authors have reported such artefacts [18,19], including recently Huang et al [10], who observed a reduction of specificity in anterior wall as an effect of AC. Such artefacts are thought to be the effect of overcorrection of the inferior wall [18,19], causing a relative reduction of counts in anterior wall, leading to induction of false perfusion defects.…”
Section: Discussionsupporting
confidence: 55%
“…This inconsistency of results should be attributed to the high complexity of the method and several sources of variability: the geometry, the kind of transmission source, the software applied for tomographic reconstruction of a study, the structure of the studied group of patients (percentage of patients with negative results of coronary angiography or low probability of CAD), and the methods applied for interpretation of studies. Moreover, many authors use only AC [1,4,9,10,12] while others also apply scatter correction [2,5,13,14] and resolution recovery [13]. In this multitude of factors affecting results of clinical studies it is very difficult to determine the real effect of AC on diagnostic efficacy of detection of CAD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations